Therapeutic drug monitoring for cytotoxic anticancer drugs: Principles and evidence-based practices - Smita, Pattanaik; Narayan, Patil Amol; J, Kumaravel; Gaurav, Prakash (Frontiers in Oncology, 2022)
Cytotoxic drugs are highly efficacious and also have low therapeutic index. A great degree of caution needs to be exercised in their usage. To optimize the efficacy these drugs need to be given at maximum tolerated dose which leads to significant amount of toxicity to the patient. The fine balance between efficacy and safety is the key to the success of cytotoxic chemotherapeutics. However, it is possibly more rewarding to obtain that balance for this class drugs as the frequency of drug related toxicities are higher compared to the other therapeutic class and are potentially life threatening and may cause prolonged morbidity. Significant efforts have been invested in last three to four decades in therapeutic drug monitoring (TDM) research to understand the relationship between the drug concentration and the response achieved for therapeutic efficacy as well as drug toxicity for cytotoxic drugs. TDM evolved over this period and the evidence gathered favoured it’s routine use for certain drugs. Since, TDM is an expensive endeavour both from economic and logistic point of view, to justify it’s use it is necessary to demonstrate that the implementation leads to perceivable improvement in the patient outcomes. It is indeed challenging to prove the utility of TDM in randomized controlled trials and at times may be nearly impossible to generate such data in view of the obvious findings and concern of compromising patient safety. Therefore, good quality data from well-designed observational study do add immense value to the scientific knowledge base, when they are examined in totality, despite the heterogeneity amongst them. This article compiles the summary of the evidence and the best practices for TDM for the three cytotoxic drug, busulfan, 5-FU and methotrexate. Traditional use of TDM or drug concentration data for dose modification has been witnessing a sea change and model informed precision dosing is the future of cytotoxic drug therapeutic management.